Immunotherapy Foreword 2018. (23rd November 2018) - Gregg, Mike
To all of our readers, the Future Medicine editorial office would like to thank you for your continued readership over 2018 and I hope you have a fantastic Christmas and New Year. I would also like to thank our esteemed editorial board, peer reviewers and contributing authors for their continued support. We very much look forward to working with you all in 2019 and seeing the journal continue to progress. In this foreword, we will present some highlights from the last 12 months in addition to looking forward to the year ahead.